2023
DOI: 10.1039/d2fo03006c
|View full text |Cite
|
Sign up to set email alerts
|

Eucommia ulmoides male flower as a remarkable edible floral resource exerts lifespan/healthspan-promoting effects on Caenorhabditis elegans

Abstract: Natural products, especially phytochemicals, can effectively improve the health of various model organisms and ultimately prolong their lifespan. As an emerging resource of plant-based food, edible flowers have potential anti-aging...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 49 publications
1
19
0
Order By: Relevance
“…Lifespan assay was performed according to the protocol described in detail previously. 21 A minimum of 50 worms per strain were grown at 20 °C and transferred to a new plate daily during the reproductive phase, thereafter about every other day. Worms were gently picked with a sterilized platinum wire, observed for a response, and counted as dead when they did not respond to the touch of the platinum needle.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lifespan assay was performed according to the protocol described in detail previously. 21 A minimum of 50 worms per strain were grown at 20 °C and transferred to a new plate daily during the reproductive phase, thereafter about every other day. Worms were gently picked with a sterilized platinum wire, observed for a response, and counted as dead when they did not respond to the touch of the platinum needle.…”
Section: Methodsmentioning
confidence: 99%
“…Lipofuscin of nematodes was tested according to Chen et al 21 After 4 and 10 days of treatment, the worms were transferred to 10 mM NaN 3 solution for 10 min and placed on a slide for measurement with fluorescence microscopy. The fluorescence microscope was set at 100× magnification using a GFP filter.…”
Section: Methodsmentioning
confidence: 99%
“…The confocal fluorescence microscopy methods used to observe body-wall muscular mitochondrial morphology (strain SJ4103), LGG-1 puncta number (DA2123), intracellular localization of DAF-16 (TJ356), and in vivo mitophagy activity (IR1511) have been detailed in our previous study. 5 However, the NGM medium composition and drugs differed, as ESI Method 1 † indicated. Moreover, the RW1596 strain was used for muscle fiber observation under the GFP channel and the 40× water immersion objective.…”
Section: Fluorescence Microscopy Imagingmentioning
confidence: 99%
“…3,4 Moreover, we found that crude extracts from Eucommia ulmoides male flowers showed healthspan-enhancing effects, involving motility, muscle status, and mitochondrial health. 5 As a new food resource approved by China's Ministry of Health, the male flowers of E. ulmoides are traditionally consumed in tea or other food ingredients. 6 Iridoids, including aucubin (Auc), geniposide (Gen), and asperuloside, were identified as major active components of this flower.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation